UNCERTAINTY AS THE KEY FACTOR TO SELECT PROJECT MANAGEMENT TOOLS - Vladimir I. Khabarov; Vladimir V. Volodin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The paper details the research aimed at determining an effective problem solving algorithmfor development and implementation ofsearch-type projects where the result originally has noterminal parameters and is achieved with an iterative-incremental methodunder resource constraints. The paper studies practical use and applied relevance of a Cynefin concept model with respect tonon-traditional projects implementedunder varying degrees of uncertainty. It definesthe concept model domainshaving different solution algorithms andmeant for various types of projects. The paper also examines application of diverse sets of rules (standards), regulations, and concept modelsto manage different types of projects. It analyzes andsubstantiates dissimilarity of theCynefin concept model that has no distinct classification features fromthe traditional modelsthat can be classified according to certain criteria and bases. The paper provides classification of projectsby their complexity and uncertainty. It presents areas of application both ofagile project management methodsandcreative technologies and approaches to complex organizational and technical, innovative, andresearch problems.